Myocardial T2 values by a segmental approach with healthy ageing and gender. (13th July 2021) - Pepe, A; Martini, N; Positano, V; D"angelo, G; Barison, A; Todiere, G; Grigoratos, C; Keilberg, P; Pistoia, L; Gargani, L; Ripoli, A; Meloni, A
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction. No data are available in literature about normal ranges for T2 in human myocardium using GE scanners. Aims. Our aims were to obtain myocardial regional and global T2 values as a reference for normality for the first time using a GE scanner and to assess their association with physiological variables. Methods. A stratified approach was adopted for healthy volunteers recruitment, ensuring the presence of 10 participants for both genders in each age decile:  20–30, 30–40, 40-50, 50-60, 60-70 years. Basal, medium, and apical short-axis slices of the left ventricle were acquired by a multi-echo fast-spin-echo (MEFSE) sequence. Image analysis was performed with a commercially available software package. T2 value was assessed in all 16 myocardial segments and global value was the mean. Results. The global T2 value averaged across all subjects was 52.2 ± 2.5 ms (range: 47.0-59.9 ms). Inter-study, intra-observer, and inter-observer reproducibility was good (coefficient of variation < 5%). The 3.6% of segments was excluded because of artifacts and/or partial-volume effects. Segmental T2 values differed significantly (P < 0.0001), with the lowest value in the basal anterolateral segment (50.0 ± 3.5 ms) and the highest in the apical lateral segment (54.9 ± 5.1 ms). Mean T2 was significantly lower in the basal slice compared to both medium (51.0 ± 2.4  vs 51.8 ± 2.6 ms; P < 0.0001) and apical slices (51.0 ± 2.4  vs 54.2 ± 3.7 ms; P < 0.0001), and in the medium slice than in the apical slice (51.8 ± 2.6  vs 54.2 ± 3.7 ms; P < 0.0001). Aging was associated with increased segmental and global T2 values. Females showed higher T2 values than males. T2 values were not correlated to heart rate. Mean T2 values, standard deviation, and lower and upper limits of normal for all 16 myocardial segments are shown in Figure 1 for males and in Figure 2 for females, considering separately each age group. Conclusion. The optimized MEFSE sequence allows for robust, reliable, and reproducible quantification of segmental T2 values. T2 values differ among myocardial slices and are influenced by age and gender, making mandatory to define gender- and age-specific segmental reference values for distinguishing between healthy and diseased myocardium. The normal ranges defined in this study on a large cohort of healthy subjects could be used as reference by other sites using the same sequence, allowing them to recruit a smaller population and accelerating the spread of myocardial T2 mapping in the clinical arena.